SOFTWARE APPLICATION TO ASSIST TEACHER PRACTICE IN TEACHING TWO-VARIABLE LINEAR PROGRAMMING: the use of graphic semiotic representations to support the learning of the deterministic algorithm for solving two-variable linear programming problems - Comelli, Caio Francisco; Sprovieri, Paulo Franciisco (Revista Interface Tecnológica, 2022)
This article aims to highlight the importance of the role of graphical semiotic representations in teaching a deterministic algorithm, purely logical and algebraic, for solving two-variable linear programming problems. To facilitate the teacher practice, an application software was built that creates, from a linear programming problem, LPP, provided by the user, a screen containing three graphical semiotic representations that seek to provide an understanding of the deterministic algorithm and, at the same time, compare with the graphic resolution previously studied. This creates an opportunity for students to develop computer programs for solving two-variable linear programming problems without the need to know graphic libraries offered by the programming environment used, which allows the development of programs that implement optimization algorithms even by students with little experience in computer programming practice. Some advantages will be presented in the use of the proposed application by the teacher responsible for presenting such contents in subjects offered in courses in the area of ​​information technology, courses in the area of ​​production and courses in the area of ​​administration.